Jumping to Conclusions: Things are Never What They Seem - Sarah Broder (Canadian Respiratory Journal)
A 46-year-old Aboriginal man presented with a massive pleural effusion. A diagnosis of sarcoidosis was established. To the author's knowledge, this is the first reported case of sarcoidosis in a North American Aboriginal patient.